1986
DOI: 10.5271/sjweh.2100
|View full text |Cite
|
Sign up to set email alerts
|

Impaired odor perception in tank cleaners.

Abstract: AHLSTROM R, BERGLUND B, BERGLUND U, LINDVALL T, WENNBERG A . Impa ired odor percept ion in tank cleaners. Scand J Work Environ Health 12 (1986) 574-581. The olfa ctor y perception of 20 men (tank cleaner s) exposed to petroleum products (while cleaning oil tanks) was examined . Offi ce workers and watchmen were used as referents (N = 20 + 20). They were matched with regard to sex, age, and smok ing habit s. Odor detection thresholds and the perceived odo r intensity of four odorous stimuli, pyridine, dimethyl … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
18
1
2

Year Published

1988
1988
2015
2015

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(21 citation statements)
references
References 14 publications
0
18
1
2
Order By: Relevance
“…Occupational exposure to styrene affected sensitivity to styrene, but this effect is expected and consistent with specific, exposure-induced effect of adaptation-which can be observed in a variety of field settings and also in the laboratory following even brief exposures to volatile chemicals [Ä hlstrom et al, 1986;Dalton and Wysocki, 1996;Wysocki et al, 1997]. The present study revealed, however, that this exposure-related decrement was more pronounced among older workers than younger ones.…”
Section: Discussioncontrasting
confidence: 53%
“…Occupational exposure to styrene affected sensitivity to styrene, but this effect is expected and consistent with specific, exposure-induced effect of adaptation-which can be observed in a variety of field settings and also in the laboratory following even brief exposures to volatile chemicals [Ä hlstrom et al, 1986;Dalton and Wysocki, 1996;Wysocki et al, 1997]. The present study revealed, however, that this exposure-related decrement was more pronounced among older workers than younger ones.…”
Section: Discussioncontrasting
confidence: 53%
“…A concurrent study on many of these same individuals revealed that detection and irritation thresholds for another substance, 1-butanol, did not differ as a function of exposure to acetone . Although exposure to some organic solvents has been correlated with more general olfactory impairments [Ahlström et al, 1986;Schwartz et al, 1989], no such effect was found from long-term exposure to acetone. The lack of general olfactory dysfunction following occupational exposure to acetone is consistent with the failure to observe gross morphological changes in the olfactory epithelium following chronic acetone exposure [Morgott, 1993].…”
Section: Discussionmentioning
confidence: 88%
“…7,9,10 Para a maioria dos diferentes grupos de compostos químicos suspeitos de serem neurotóxicos, as propriedades ototóxicas nunca foram testadas. 1,2,11 Entre esses grupos estão os agrotóxicos. Estima-se que dos 600 princípios ativos de pesticidas mundialmente disponível no mercado, 50 mil formulações comerciais são utilizadas na agricultura.…”
Section: Introductionunclassified